Selective M3 Muscarinic Receptor Antagonist Inhibits Small-Cell Lung Carcinoma Growth in a Mouse Orthotopic Xenograft Model - Nozomi Ami; Kazumi Koga; Hiroshi Fushiki; Yoko Ueno; Yoshio Ogino; Hisashi Ohta (Elsevier, 2011)
Abstract.: In small cell lung carcinoma (SCLC), acetylcholine (ACh) is synthesized and secreted, and it acts as an autocrine growth factor through activation of its receptors, muscarinic receptor (mAChR) and nicotinic receptor (nAChR). Alteration of tumor growth by blockade of M3 mAChR in a human SCLC cell line, NCI-H82, was investigated in the present study. We used a highly selective M3 muscarinic antagonist, N-(2-[3-([3R]-1-(cyclohexylmethyl)-3-piperidinyl]methylamino)-3-oxopropyl]amino-2-oxoethyl)-3,3,3-triphenyl-propioamide (J-115311). Our results show that J-115311 inhibited the increased intracellular calcium elicited by carbachol, a muscarinic agonist, in SCLC cells. J-115311 also inhibited SCLC cell growth in vitro. In a mouse orthotopic xenograft model, J-115311 dose-dependently reduced tumor growth when NCI-H82 cells were inoculated into the upper left lobe of the lung. These findings indicate that blockade of M3 mAChR can suppress tumor growth in SCLC, suggesting the potential therapeutic utility of M3 muscarinic antagonists as anti-cancer agents. Keywords:: selective M3 muscarinic antagonist, M3 muscarinic receptor, small cell lung carcinoma, orthotopic xenograft model, non-neuronal cholinergic system